Unemployment insurance in the United States : analysis of policy issues - O'Leary, Christopher J.; Wandner, Stephen A. (W.E. Upjohn Institute for Employment Research, 1997)
Discusses the unemployment insurance system in which programmes are operated by each state within the minimum standards established by the federal government.